2019
DOI: 10.3904/kjim.2016.194
|View full text |Cite
|
Sign up to set email alerts
|

Application of therapeutic plasma exchange in patients having severe fever with thrombocytopenia syndrome

Abstract: Background/Aims Severe fever with thrombocytopenia syndrome (SFTS) is a viral hemorrhagic fever with a high fatality rate. However, effective treatments for SFTS cases not responded to supportive therapy have not been established. Herein, we introduced the therapeutic plasma exchange (TPE) in SFTS patients in a tertiary hospital between 2013 and 2015. Methods TPE was performed in patients with rapidly progressing SFTS. Clinical, laboratory, and virological parameters we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 26 publications
0
34
0
2
Order By: Relevance
“…And a previous research had reported that the majority of SFTS (86%) are detected in subjects 50 years of age or older ( Liu et al, 2015 ), which is same with our finding. Previous studies had pay attention to the ecology and transmission cycle ( Wang et al, 2015 ; Li et al, 2016 ), pathogenesis ( Wu et al, 2014 ; Ning et al, 2015 ; Silvas et al, 2015 ) and treatment ( Kim et al, 2016 ; Yoo et al, 2017 ) of SFTS, but no one has pointed to the alteration of gut microbiota for SFTS patients, this study aim to find some differences of gut microbiome between SFTS patients and health people.…”
Section: Discussionmentioning
confidence: 99%
“…And a previous research had reported that the majority of SFTS (86%) are detected in subjects 50 years of age or older ( Liu et al, 2015 ), which is same with our finding. Previous studies had pay attention to the ecology and transmission cycle ( Wang et al, 2015 ; Li et al, 2016 ), pathogenesis ( Wu et al, 2014 ; Ning et al, 2015 ; Silvas et al, 2015 ) and treatment ( Kim et al, 2016 ; Yoo et al, 2017 ) of SFTS, but no one has pointed to the alteration of gut microbiota for SFTS patients, this study aim to find some differences of gut microbiome between SFTS patients and health people.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the high awareness within the medical community in SFTS-endemic areas, and the use of antiviral therapy such as ribavirin, the case fatality rate of SFTS is still as high as 15%, which is the same as other severe viral diseases including viral hemorrhagic fevers (15). In SFTS, inflammatory cytokine storms (11,(16)(17)(18)(19) as well as impairment of immune responses including innate immunity (14,(20)(21)(22)(23)(24)(25), antiviral T cell function (26), and antiviral humoral responses (27) have important roles in the pathogenic progress of lethal infections. Immune impairment and high viral loads are also characteristics of several other viral hemorrhagic fevers (28), but these diseases differ in terms of pathology and pathogenesis, about which little is known for SFTS.…”
Section: Introductionmentioning
confidence: 99%
“…The development of specific treatment for SFTS is crucial because SFTSV infection is relatively rare and the affected patients are mainly elderly. Some proposed treatments for SFTS include steroid pulse therapy (Nakamura et al, 2018), plasma exchange (Oh et al, 2014;Yoo et al, 2019), and antiviral drugs (Saijo, 2018); however, their effectiveness remains unclear.…”
Section: Introductionmentioning
confidence: 99%